Aspek Perlindungan Hukum Terhadap Nasanah Atas Penyelenggaraan E-Payment Berbasis QR-Code - I Putu Rasmadi Arsha Putra; Dewa Gede Pradnya Yustiawan (Kertha Wicaksana, 2022)
The development of an e-payment system that uses QR-Code as an effective payment method and is proven to have efficiency, but the efficiency and effectiveness offered raises problems in the community related to security regarding this QR-Code method. Analyzing legal protection to customers in the use of the QR-Code method in transactions is the goal of this research. This study uses a normative method, using a statutory approach and a legal concept analysis approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials that are systematically collected and traced by documentation studies and supplemented with supporting data. All legal materials collected were analyzed by descriptive analysis technique. This study found several regulations governing e-payment and QR-Code which are still scattered in several regulations, this of course confuses customers as consumers regarding legal protection. So that in the application of e-payment in which there is a QR-Code as one of the methods, special rules need to be made, besides that customers as consumers are expected to educate themselves related to payment technology so that they are not harmed materially or immaterially if in practice the implementation of the QR-Code does not heed consumer rights. It can be concluded that with a study on legal protection against the implementation of QR-Code-based e-payments, customers can protect their rights as consumers.